The Performance of Dynamic-static Spectrum Access Based on Markov Transfer Model - Changbiao Xu; Lianjun Zhu (Institute of Advanced Engineering and Science, 2016)
This study presented a non-synchronized random access mechanism that supports dynamic-static spectrum. Generally, the authorized users of two networks (network A and network B) with different frequency bands communicate with each other by using static spectrum. When congestion happened, spectrum holes in their networks can be detected by the opposite networks and then utilized to communicate. Based on queuing theory and Markov transfer model, a user behavior characterized by dynamic-static spectrum access was proposed, and the feasibility of this theoretical model was validated through analog simulation. Thereafter, the theoretical parameters of system performance, like blocking possibility, forced drop-call possibility, and throughput, were measured and compared between dynamic-static mode and unconjugated mode.